Tellurides and native elements in copper-zinc ores of manifestations «Zapadnoe» (Subpolar Urals, Russia) - Kudrin, Konstantin Yu.; Starikov, Andrey; Korzshov, Yuriy (Revista de la Universidad del Zulia, 2019)
Background: Previously conducted mineralogical and geochemical studies of copper-zinc ores manifestations «Zapadnoe» showed that the feature of pyrrhotite, pyrite, chalcopyrite and sphalerite is an increased content of Ag and industrially significant Au content, as well as the appearance of silver-containing sphalerite. The purpose of this study is to establish the mineralogical form of noble metals in ores. Methods: Mineralogical studies were conducted using an electronic scanning microscope JSM-6510LV (Jeol Ltd). 13 samples taken from the core of the wells were studied: 954 determinations of the ore-forming minerals were made, 140 of them recorded the presence of precious metals. Results: Precious metals – gold and silver – tellurides are mainly: hessite, stutzite, volynskite, matildite, cervelleite, petzite and sylvanite; rarely native gold. The host mineral matrix is most often sulfides: sphalerite, pyrrhotite, chalcopyrite, pyrite; rarely – galena. Conclusion: The angular, xenomorphic form of separation of aggregates and the consistency of the mineral composition of telluride mineralization can be the result of crystallization of a relatively low-temperature melt among thermally more stable silicate and sulfide phases